2023
DOI: 10.3390/plants12101974
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition of Cranberry (Vaccinium oxycoccos L.) Fruits Growing in Protected Areas of Lithuania

Rima Šedbarė,
Sigita Sprainaitytė,
Gintaras Baublys
et al.

Abstract: The fruits of Vaccinium oxycoccos L. are an important source of bioactive compounds with antibacterial, antifungal, and anti-inflammatory effects. Studies on the phytochemical analysis of cranberry fruit samples showed that the qualitative and quantitative composition of biologically active compounds varied in cranberry fruit samples collected from different types of wetland sites: the total anthocyanin content was 698 ± 24–8352 ± 200 µg/g, the total flavonol content—518 ± 16–2811 ± 31 µg/g, the total content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…They are usually responsible for the red, blue and purple colour of fruits and vegetables [ 45 , 46 ]. Fresh raspberry (2199.0 mg/100 g) [ 47 ], cranberry (835.2 mg/100 g) [ 48 ] and chokeberry (686.0 mg/100 g) [ 49 ] have the highest total anthocyanin contents. Other studies have indicated the following contents in whole fruit: a maximum of 22.1 mg/100 g in fresh red currants [ 50 ]; approximately 465.4 mg anthocyanins/100 g (as cyanidin-3-glucoside equivalents) in blackberries [ 51 ]; 204.3 mg anthocyanins/100 g in strawberries [ 52 ]; 287.8 mg/100 g in blackcurrants [ 50 ]; 344.9 mg/100 g in cherries [ 53 ]; and 534.2 mg/100 g in blueberries [ 54 ].…”
Section: The Occurrence and Content Of Anthocyanins In Fruits And Veg...mentioning
confidence: 99%
“…They are usually responsible for the red, blue and purple colour of fruits and vegetables [ 45 , 46 ]. Fresh raspberry (2199.0 mg/100 g) [ 47 ], cranberry (835.2 mg/100 g) [ 48 ] and chokeberry (686.0 mg/100 g) [ 49 ] have the highest total anthocyanin contents. Other studies have indicated the following contents in whole fruit: a maximum of 22.1 mg/100 g in fresh red currants [ 50 ]; approximately 465.4 mg anthocyanins/100 g (as cyanidin-3-glucoside equivalents) in blackberries [ 51 ]; 204.3 mg anthocyanins/100 g in strawberries [ 52 ]; 287.8 mg/100 g in blackcurrants [ 50 ]; 344.9 mg/100 g in cherries [ 53 ]; and 534.2 mg/100 g in blueberries [ 54 ].…”
Section: The Occurrence and Content Of Anthocyanins In Fruits And Veg...mentioning
confidence: 99%
“…The analysis of the qualitative and quantitative composition of anthocyanins in bog cranberries growing in the territories of the Žuvintas and Kamanai State Strict Nature Reserves in Lithuania showed that the percentage of anthocyanins in cranberry fruit samples varied depending on the location of the plant. Four anthocyanins were predominant in cranberry fruit samples harvested from different wetland habitats (cyanidin-3-O-galactoside, cyanidin-3-O-arabinoside, peonidin-3-Ogalactoside, and peonidin-3-O-arabinoside), while six anthocyanins predominated in others (cyanidin-3-O-galactoside, cyanidin-3-O-arabinoside, peonidin-3-O-galactoside, peonidin-3-O-arabinoside, cyanidin-3-O-glucoside, and peonidin-3-O-glucoside) [15].…”
Section: Analysis Of the Qualitative And Quantitative Composition Of ...mentioning
confidence: 99%
“…We found that the total anthocyanin content varied among the fruit samples harvested: 710.3 ± 40 µg/g to 6054.5 ± 200 µg/g in the 2020 growing season, 779.0 ± 12 µg/g to 6993.8 ± 119 µg/g in 2021, and 974.8 ± 23 µg/g to 6840.9 ± 185 µg/g in 2022 (Figure 2). The anthocyanin content of cranberry fruit samples harvested in 2021 in the Kamanai and Žuvintas State Strict Nature Reserves varied over a wider range, from 698 ± 24 µg/g to 8352 ± 200 µg/g [15].…”
Section: Analysis Of the Qualitative And Quantitative Composition Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The phytochemical composition of small and large cranberry fruits is influenced by genetic and environmental factors, and the composition of their extracts is determined by the extraction conditions and applied extraction methods [ 19 , 20 ]. It was found that the profiles of anthocyanins, flavonols, and triterpene compounds in small cranberry and large cranberry fruit samples were quite similar, but the quantitative composition of bioactive compounds in cranberry fruits varies [ 21 , 22 , 23 ]. Jungfer et al found that the concentration of A-trimeric proanthocyanidins in V. macrocarpon fruits was up to 15 times higher than in V. oxycoccos fruits [ 24 ].…”
Section: Introductionmentioning
confidence: 99%